Respuesta :
y = 2x² - 4x - 5
substitute x = -3 to the equation
y = 2 · (-3)² - 4 · (-3) - 5 = 2 · 9 + 12 - 5 = 18 + 12 - 5 = 30 - 5 = 25
Answer: y = 25
substitute x = -3 to the equation
y = 2 · (-3)² - 4 · (-3) - 5 = 2 · 9 + 12 - 5 = 18 + 12 - 5 = 30 - 5 = 25
Answer: y = 25
The value of the quadratic equation, y = 2x² – 4x – 5 at x = –3, will be 25.
What is a quadratic equation?
The quadratic equation is given as ax² + bx + c = 0. Then the degree of the equation will be 2. Then we have
The quadratic equation is given below.
y = 2x² – 4x – 5
At x = -3, then the value of y will be
y = 2(–3)² – 4(–3) – 5
y = 18 + 12 – 5
y = 25
More about the quadratic equation link is given below.
https://brainly.com/question/2263981
#SPJ2